HYGIENE BEHAVIOR OF HOUSEHOLD WASTE MAKING IN KALISARI PURWOKERTO UTARA BANYUMAS DISTRICT - Heryanto, Heryanto (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Background: Efforts to prevent and reduce mortality due to disease, each individual is required to have habits in daily life, namely to carry out personal hygiene in accordance with hygiene and health standards. The work of taking household waste in the Kalisari area has the potential risk of being exposed to various kinds of occupational diseases that every day interact with garbage, so that individual hygiene behavior is needed to prevent the risk of work activities. Research Methods: This study used a qualitative descriptive approach using the technique of determining the purposive sampling and snow ball samples. To obtain data the researcher used in-depth interview and observation techniques, while to obtain valid data information the research used data triangulation, sources and methods. In an effort to explore information about individual hygiene, workers taking household waste researchers used research subjects. The research subjects were 5 workers with one constellation or the data had reached a saturation point and did not vary anymore. Results: From the results of research on the personal hygiene of garbage collection workers, workers have not been able to definitively understand individual hygiene knowledge. The attitude of the workers supports supporting individual hygiene and some have used PPE, namely bood hat shoes. Sarana prsarana at work, not all workers use the complete work attributes, namely PPE. Puskermas Officer in this case sanitarian officer provides counseling in an effort to provide personal hygiene information.